Single-molecule studies of disulfide bond reduction pathways used by human thioredoxin - Szoszkiewicz, Robert (My University, 2013)
Disulfide bond reduction pathways used by human thioredoxin (hTrx) are studied at the single molecule level using a recombinant protein (I27[subscript SS])[subscript 8]. (I27[subscript SS])[subscript 8] contains eight tandem repeats of identical immunoglobulin-like modules with one disulfide bond in each module. Single (I27[subscript SS])[subscript 8] molecules are stretched at constant force applied by a cantilever in a force-clamp mode of atomic force microscopy (FC-AFM). Disulfide reduction events are accurately detected from stepwise increases in the end-to-end length of (I27[subscript SS])[subscript 8]. Earlier FC-AFM studies observed one disulfide reduction pathway used by hTrx and suggested an additional electron tunnelling mechanism. Here, a very large set of unbiased FC-AFM data is collected in a range of clamping forces. By analyzing the data using exponential fits and dwell times histograms two disulfide reduction pathways used by hTrx are resolved. Based on previous studies one of these pathways is attributed to force-dependent Michaelis-Menten catalysis. The latter reduction pathway is weakly force-inhibited and occurs sporadically. Bimolecular nucleophilic substitutions (S[subscript N]2) and electron tunnelling (ET) mechanisms are discussed to explain the second pathway. Direct S[subscript N]2 and ET mechanisms cannot be discounted, but a hypothetical E2-S[subscript N]2 mechanism involving a hydride reducing a disulfide bond provides an interesting alternative, which needs to be verified in future experiments.
Keywords: Atomic force microscopy; Single molecule biophysics; Protein chemistry; Disulfide bond reduction; Thioredoxin; Enzyme kinetics; Ensemble kinetic analysis; Dwell time histograms